SCIENCE EDUCATION IN SOMALIA: FOSTERING CHILDREN'S EARLY CONNECTION WITH NATURE - Manojkumar J (CV. Fahr Publishing, 2025)
This study aims to investigate the impact of nature-based science education on primary school children in Somalia, focusing on both their scientific inquiry skills and development of ecological identity. The research employs a systematic literature review methodology, synthesizing empirical and theoretical studies published in the last five years, including interventions, outdoor learning programs, and teacher-mediated strategies. Data were collected from peer-reviewed journals and analyzed through descriptive statistics and thematic synthesis to identify key factors influencing learning outcomes, such as teacher preparation, resource availability, and culturally contextualized activity design. The findings indicate that structured nature-based activities significantly enhance children’s observation, hypothesis formulation, problem-solving abilities, and their connection to the natural environment. Teacher facilitation and the integration of local ecological contexts were found to be critical moderators for achieving meaningful gains. This study contributes novel insights by focusing on an under-researched, low-resource setting while linking inquiry skill development with ecological identity formation, offering a culturally and contextually relevant perspective rarely addressed in the literature. Furthermore, it provides actionable guidance for educators and policymakers on implementing effective outdoor science programs in resource-constrained primary schools. In conclusion, the research demonstrates that embedding nature in science education is not merely supplementary but fundamental to promoting scientific literacy and sustainable environmental awareness among children. These insights have implications for global educational practice, particularly in regions facing environmental and infrastructural challenges, suggesting that contextually adapted, nature-infused curricula can yield significant cognitive and affective benefits in early science education.